Students’ Attitude towards Wattpad as an Online Reading Platform: Is It Favorable or Not? - Safriyani, Rizka; Mufidah, Rania (English Department, Universitas Negeri Surabaya, 2022)
Wattpad is a free application for reading and writing short stories. Users are able to leave comments directly within the paragraphs of the short story. This study aims to examine the students' attitudes on Wattpad as an online story reading platform and the varieties of genres on Wattpad as an online story reading platform, as well as. As a case study, qualitative research was utilized in this study. Thirty seven undergraduate students from UIN Sunan Ampel Surabaya who use Wattpad for online story reading participated in this study. The instruments were adapted from Ganie et all. The result indicates both favorable and unfavorable opinions towards Wattpad as an online reading platform. Moreover, the results show that participants favor to read romance story and many participants unfavor to read mistery and science fiction story. Implication and recommendations are suggested.